2015
DOI: 10.1002/jbt.21698
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates l‐Arginine‐Induced Pancreatitis and Associated Fibrosis in Wistar Rat: Role of Inflammation and Nitrosative Stress

Abstract: Several reports indicated that histone deacetylases (HDACs) play a crucial role in inflammation and fibrogenesis. Sodium butyrate (SB) is a short-chain fatty acid having HDAC inhibition potential. The present study aimed to evaluate the protective effect of SB against L-arginine (L-Arg)-induced pancreatic fibrosis in Wistar rats. Pancreatic fibrosis was induced by twice intraperitoneal (i.p.) injections of 20% L-Arg (250 mg/100 g) at 2-h interval on day 1, 4, 7, and 10, whereas SB (800 mg/kg/day) was administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 50 publications
1
32
0
1
Order By: Relevance
“…Although, butyrate is a nonselective HDACi and preferably inhibited class I and II HDACs at millimolar concentrations, thereby modulates the wide range of cellular and molecullar signaling/pathways [38,42]. Further, it is postulated that two molecule of butyrate can inhibit HDACs by occupying its hydrophobic pocket as similar with the trichostatin A [62,92]. However, the exact mechanism of HDAC inhibition by butyrate is yet to be explored.…”
Section: Advantages and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although, butyrate is a nonselective HDACi and preferably inhibited class I and II HDACs at millimolar concentrations, thereby modulates the wide range of cellular and molecullar signaling/pathways [38,42]. Further, it is postulated that two molecule of butyrate can inhibit HDACs by occupying its hydrophobic pocket as similar with the trichostatin A [62,92]. However, the exact mechanism of HDAC inhibition by butyrate is yet to be explored.…”
Section: Advantages and Limitationsmentioning
confidence: 96%
“…NF-κB modulates the expression of genes encoding the proinflammatory cytokines, chemokines, inducible nitric oxide synthase, COX-2 and adhesion molecules [47]. The anti-inflammatory effect of butyrate is mainly exerted by the inhibition of NF-κB, decreased myeloperoxidase and COX-2 expression [61,62]. Another recent study demonstrates the anti-inflammatory and immunomodulatory effects of butyrate by promoting functional regulatory T cells via epigenetic upregulation of the forkhead box P3 gene in colon of mice, which have a central role in the reduction of inflammatory and allergic responses.…”
Section: Review Khan and Jenamentioning
confidence: 99%
“…Based on these observations, we hypothesize that HDAC activity may be a key factor in modulating not only leukocyte infiltration in the injured tissue but also gene expression changes in acinar cells affecting pancreatic regeneration. In support of this hypothesis, two recent studies showed that in vivo treatment with the pan-HDAC inhibitors sodium butyrate and trichostatin A (TSA), which target both class I and class II HDAC subfamilies, alleviated pancreatic damage, inflammation and fibrosis following L-arginine- (Kanika et al, 2015) or taurocholic acid-induced pancreatitis (Hartman et al, 2015) in rodents. However, in another study treatment with valproic acid had a detrimental effect on cerulein-induced pancreatitis, consequently delaying tissue recovery and reducing acinar cell proliferation (Eisses et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Diabetic animal were provided HFD throughout the treatment schedule, while normal and VPA control animals were provided normal pellet diet (low-fat). The doses of NaB (400 and 800 mg/kg) and metformin were selected on the basis of previous studies [14,29,32]. Both NaB and metformin were dissolved in water and administrated according to body weight.…”
Section: Parametersmentioning
confidence: 99%